Discovery of entomopathogenic fungi across geographical regions in southern China on pine sawyer beetle Monochamus alternatus and implication for multi-pathogen vectoring potential of this beetle - Wu, Shengxin; Wu, Jia; Wang, Yun; Qu, Yifei; He, Yao; Wang, Jingyan; Cheng, Jianhui; Zhang, Liqin; Cheng, Chihang (Frontiers in Plant Science, 2022)
Entomopathogen-based biocontrol is crucial for blocking the transmission of vector-borne diseases; however, few cross-latitudinal investigations of entomopathogens have been reported for vectors transmitting woody plant diseases in forest ecosystems. The pine sawyer beetle Monochamus alternatus is an important wood borer and a major vector transmitting pine wilt disease, facilitating invasion of the pinewood nematode Bursaphelenchus xylophilus (PWN) in China. Due to the limited geographical breadth of sampling regions, species diversity of fungal associates (especially entomopathogenic fungi) on M. alternatus adults and their potential ecological functions have been markedly underestimated. In this study, through traditional fungal isolation with morphological and molecular identification, 640 fungal strains (affiliated with 15 genera and 39 species) were isolated from 81 beetle cadavers covered by mycelia or those symptomatically alive across five regional populations of this pest in southern China. Multivariate analyses revealed significant differences in the fungal community composition among geographical populations of M. alternatus, presenting regionalized characteristics, whereas no significant differences were found in fungal composition between beetle genders or among body positions. Four region-representative fungi, namely, Lecanicillium attenuatum (Zhejiang), Aspergillus austwickii (Sichuan), Scopulariopsis alboflavescens (Fujian), and A. ruber (Guangxi), as well as the three fungal species Beauveria bassiana, Penicillium citrinum, and Trichoderma dorotheae, showed significantly stronger entomopathogenic activities than other fungi. Additionally, insect-parasitic entomopathogenic fungi (A. austwickii, B. bassiana, L. attenuatum, and S. alboflavescens) exhibited less to no obvious phytopathogenic activities on the host pine Pinus massoniana, whereas P. citrinum, Purpureocillium lilacinum, and certain species of Fusarium spp.—isolated from M. alternatus body surfaces—exhibited remarkably higher phytopathogenicity. Our results provide a broader view of the entomopathogenic fungal community on the vector beetle M. alternatus, some of which are reported for the first time on Monochamus spp. in China. Moreover, this beetle might be more highly-risk in pine forests than previously considered, as a potential multi-pathogen vector of both PWN and phytopathogenic fungi.